Brain-Derived Neurotrophic Factor Mitigates the Association Between Platelet Dysfunction and Cognitive Impairment - Bélanger, Jean-Christophe; Bouchard, Véronique; Le Blanc, Jessica; Starnino, Louisia; Welman, Mélanie; Chabot-Blanchet, Malorie; Busseuil, David; Chertkow, Howard; D'Antono, Bianca; Lordkipanidzé, Marie (Frontiers in Cardiovascular Medicine, 2021)
Background: Platelet hyperactivity is deleterious in coronary artery disease (CAD), requiring lifelong antiplatelet therapy, and is associated with worse cognitive outcomes. Upon activation, platelets release Brain-Derived Neurotrophic Factor (BDNF), a neurotrophin protective against cognitive decline. Given these apparently opposing effects of platelet activation on cognitive health, we investigated whether BDNF levels intercede in the relationship between platelet activation and cognitive function; and whether this relationship is moderated by the presence of CAD. Methods: In this cross-sectional study, 1,280 participants with (n = 673) and without CAD (n = 607) completed the Montreal Cognitive Assessment (MoCA). Plasma BDNF and soluble P-selectin (a marker of platelet activity) levels were assessed using multiplex flow cytometry. Results: In a mediation model, platelet activity was correlated with higher plasma BDNF concentrations (b = 0.53, p < 0.0001). The relationship between sP-selectin and BDNF concentrations was stronger for individuals without CAD (b = 0.71, p < 0.0001) than for CAD participants (b = 0.43, p < 0.0001; pinteraction <0.0001). Higher BDNF concentrations were associated with higher MoCA scores (b = 0.26, p = 0.03). The overall effect of platelet activity on cognitive performance was non-significant (total effect: b = −0.12, p = 0.13), and became significant when accounting for BDNF as a mediating factor (direct effect: b = −0.26, p = 0.01). This resulted in a positive indirect effect of platelet activity (via BDNF) on MoCA scores (b = 0.14, CI 95% 0.02–0.30), that was smaller in CAD participants than in non-CAD participants [Δ −0.07 (95% CI −0.14 to −0.01)]. Conclusions: BDNF released from activated platelets could be a mitigating factor in a negative association between platelet activity and cognitive function.